Agile systems engineering - Douglass, Bruce Powel (Morgan Kaufmann, 2016)
Presenting a vision of systems engineering where precise specification of requirements, structure, and behavior meet larger concerns as such as safety, security, reliability, and performance in an agile engineering context, this book discusses the lifecycle of systems development, including requirements, analysis, design, and the handoff to specific engineering disciplines. --